Energy budget of first‐year Arctic sea ice in advanced stages of melt. Issue 11 (7th June 2013) - Hudson, Stephen R.; Granskog, Mats A.; Sundfjord, Arild; Randelhoff, Achim; Renner, Angelika H. H.; Divine, Dmitry V.
Abstract : [1] During an 8 day drift in July–August 2012 in the Nansen Basin, all components of the energy budget of melting first‐year sea ice were observed. Absorption of solar radiation by the ice and ponds was the largest source of energy to the ice at almost all times during the drift. However, oceanic heat flux also provided significant heating and dominated during one wind event. Longwave fluxes provided a relatively small cooling effect, and atmospheric heat fluxes were negligible. The aggregate scale albedo of this younger, thinner ice was significantly lower than at Surface Heat Budget of the Arctic Ocean (SHEBA), and the transmittance was significantly higher here, despite similar pond and open water fractions. The oceanic heat flux was only half of the solar flux through the ice to the water, producing warm water near the surface that might delay ice growth in autumn, an important effect of the transition to thinner first‐year ice in the high Arctic. Key Points: First-year sea ice reflects less and transmits more sunlight than multiyear ice The increased transmittance allows for greater ocean heat fluxes Some transmitted energy is stored, released later in the year or during storms